KEMANDIRIAN ANAK USIA PRA SEKOLAH DITINJAU DARI IBU BEKERJA DAN TIDAK BEKERJA DI TK MUTIARA DESA PILOHAYANGA KECAMATAN TELAGA - Anik Indarwati; Fadelia Duu (Elsia: Jurnal Psikologi Manusia, 2022)
Independence can make children responsible for meeting their needs and foster self-confidence. Children who have independence can adapt to the environment and make children able to learn to overcome the difficulties they face. The independence of early childhood depends on the parenting applied in the family, especially the mother. Even though the mother has a job status, it is expected that the mother can have the expertise to fulfill her obligations as a housewife. This study aims to determine whether there are differences in children's independence in working and non-working mothers in Mutiara Kindergarten, Pilohayanga Village, Telaga District, Gorontalo Regency. This study used a quantitative method. The sample in this study amounted to 45 students. The sampling technique used was random cluster sampling. This study's results show a value of 229. The value is more significant than 0.05, and the calculated f value is 1.487. It is concluded that there is a difference between the level of independence of preschool children in working and non-working mothers.